Study on the Multi-Hazard Responses of Transmission Tower-Line Systems Under Fire and Wind Loads Using ABAQUS - Xiwei He; Huichao Ma; Shibo Zhang; Wenming Wang; Lijuan Zhang (Applied Sciences)
Transmission lines are usually located outdoors and are subjected to wind loads year-round. When a fire occurs, transmission towers are exposed to the combined effects of fire and wind loads. This paper investigates the impact of high temperatures on the bearing capacity of transmission tower-line systems under wind load and explores the effects of uneven horizontal spacing distribution and changes in the elevation of the target tower on the bearing capacity of the tower-line system. The failure criteria for transmission tower components at high temperatures were determined by considering the constitutive relationship of steel at ambient temperature and the variation patterns in material strength and elastic modulus with temperature. A finite element model of the transmission tower-line system was established using ABAQUS (2023). This paper studied the effects of temperature, uneven horizontal spacing distribution, and changes in the elevation of the target tower on the response of the transmission tower-line system by comparing collapse-resisting wind speeds and collapse processes under various conditions. The research indicates that the load-bearing capacity of the transmission tower-line system decreases as temperature increases. When the temperature exceeds 400 °C, the collapse-resisting wind speed of the transmission tower drops sharply. At temperatures above 600 °C, the transmission tower may collapse even at the annual average wind speed. In addition, the uneven horizontal spacing distribution and changes in the elevation of the target tower have an adverse effect on the stability of the transmission tower-line system. It is recommended to choose steel materials with higher fire resistance or apply fire-resistant coatings to existing steel, and to avoid extremely uneven spacing distributions and excessively high target tower elevations.